Who Do Populist Radical Right Parties Stand for? Representative Claims, Claim Acceptance and Descriptive Representation in the Austrian FPÖ and German AfD. Issue 4 (2nd October 2019) - Heinisch, Reinhard; Werner, Annika
ABSTRACT: Populist radical right parties are known for focussing on a vague idea of 'the people' and rejecting social groups like immigrants. The representative relationship between parties and voters, however, is a positive one. Thus, this article investigates (a) who populist radical right parties claim to represent, (b) whether these groups accept the claim, and (c) whether the parties indeed represent these groups descriptively. Our analysis of the manifestos, voters and parliamentary groups of the Austrian Freedom Party and the Alternative for Germany shows, first, that these parties have markedly different conceptualisations of 'the people'. Further, we find that both parties claim to represent native families, pensioners, members of the police and armed forces as well as inhabitants of rural areas. While most of these groups reject this representative claim in both countries, the AfD and, to a lesser extent, the FPÖ indeed represent these population segments in the parliaments. Thus, this article contributes to our understanding of populist radical right parties' roles in representative democracies by identifying a gap between these parties' representative claims towards social groups and those groups' voting behaviour.